Flavin Electron Shuttles Dominate Extracellular Electron Transfer by Shewanella oneidensis - Kotloski, Nicholas J.; Gralnick, Jeffrey A. (mBio, 2013)
Shewanella oneidensis strain MR-1 is widely studied for its ability to respire a diverse array of soluble and insoluble electron acceptors. The ability to breathe insoluble substrates is defined as extracellular electron transfer and can occur via direct contact or by electron shuttling in S. oneidensis . To determine the contribution of flavin electron shuttles in extracellular electron transfer, a transposon mutagenesis screen was performed with S. oneidensis to identify mutants unable to secrete flavins. A multidrug and toxin efflux transporter encoded by SO_0702 was identified and renamed bfe ( b acterial f lavin adenine dinucleotide [FAD] e xporter) based on phenotypic characterization. Deletion of bfe resulted in a severe decrease in extracellular flavins, while overexpression of bfe increased the concentration of extracellular flavins. Strains lacking bfe had no defect in reduction of soluble Fe(III), but these strains were deficient in the rate of insoluble Fe(III) oxide reduction, which was alleviated by the addition of exogenous flavins. To test a different insoluble electron acceptor, graphite electrode bioreactors were set up to measure current produced by wild-type S. oneidensis and the Δ bfe mutant. With the same concentration of supplemented flavins, the two strains produced similar amounts of current. However, when exogenous flavins were not supplemented to bioreactors, bfe mutant strains produced significantly less current than the wild type. We have demonstrated that flavin electron shuttling accounts for ~75% of extracellular electron transfer to insoluble substrates by S. oneidensis and have identified the first FAD transporter in bacteria. IMPORTANCE Extracellular electron transfer by microbes is critical for the geochemical cycling of metals, bioremediation, and biocatalysis using electrodes. A controversy in the field was addressed by demonstrating that flavin electron shuttling, not direct electron transfer or nanowires, is the primary mechanism of extracellular electron transfer employed by the bacterium Shewanella oneidensis . We have identified a flavin adenine dinucleotide transporter conserved in all sequenced Shewanella species that facilitates export of flavin electron shuttles in S. oneidensis . Analysis of a strain that is unable to secrete flavins demonstrated that electron shuttling accounts for ~75% of the insoluble extracellular electron transfer capacity in S. oneidensis . Extracellular electron transfer by microbes is critical for the geochemical cycling of metals, bioremediation, and biocatalysis using electrodes. A controversy in the field was addressed by demonstrating that flavin electron shuttling, not direct electron transfer or nanowires, is the primary mechanism of extracellular electron transfer employed by the bacterium Shewanella oneidensis . We have identified a flavin adenine dinucleotide transporter conserved in all sequenced Shewanella species that facilitates export of flavin electron shuttles in S. oneidensis . Analysis of a strain that is unable to secrete flavins demonstrated that electron shuttling accounts for ~75% of the insoluble extracellular electron transfer capacity in S. oneidensis .